Improving the Quality of Islamic Education through Pesantren-Based Management in Indonesia - Yugo, Tri (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
Islamic education in Indonesia faces a significant challenge in maintaining quality and relevance amid globalization and technological disruption. Although pesantren plays a central role in shaping Islamic character, there is still limited study of the effectiveness of pesantren-based management in improving the quality of education. This study aims to examine how pesantren-based management models integrate Islamic values into the governance of educational institutions to strengthen the quality of Islamic education. This study uses a qualitative approach based on a literature study, by examining relevant scientific and policy literature to analyze the contribution of pesantren-based management to improving the quality of Islamic education. The findings suggest that this model focuses on three main aspects: (1) Islamic leadership; (2) integrative curriculum management; and (3) community-based collective participation. The three encourage technology-based learning innovation, establishing autonomous business units, and strengthening teacher capacity. However, significant challenges such as limited human resources, unequal access to technology, and resistance to change remain significant obstacles. This study concludes that pesantren-based management remains relevant as a strategy to improve the quality of Islamic education, which is rooted in traditional values but adaptive to change. The implication is that strategic partnerships between Islamic boarding schools, the government, and external partners are needed to support the sustainability and expansion of the impact of this transformation.